Climate change and migration dynamics in Somalia: a time series analysis of environmental displacement - Mohamed, Abdikadir Ahmed; Omar, Ibtisam Mohamed; Yusuf Ibey, Abdi Majid; Omar, Mahdi Mohamed (Frontiers in Climate, 2025)
Climate change is a significant driver of human migration, especially in vulnerable regions like Somalia. This study investigates the relationship between climate variables—average annual precipitation, temperature, and CO₂ emissions—and net migration in Somalia, using time series data from 1990 to 2020. Additionally, it examines the role of population growth as a factor influencing migration. Applying the Autoregressive Distributed Lag (ARDL) model, this research captures both short- and long-term dynamics, providing insights into how environmental and demographic factors impact migration in this climate-sensitive region. The results indicate that favorable rainfall conditions positively influence net migration, as improved agricultural productivity stabilizes livelihoods, reducing pressures to migrate. In contrast, increased CO₂ emissions, associated with environmental degradation, negatively impact migration by limiting financial capacity, creating a “trapped population” effect. Population growth also intensifies migration pressures by increasing competition for limited resources. Interestingly, temperature variations do not significantly influence migration, possibly due to adaptive strategies or resilience to temperature fluctuations in the region. These findings underscore the need for policies focused on enhancing agricultural resilience, restoring degraded environments, and creating economic opportunities to reduce migration pressures in Somalia. Investments in sustainable land use, climate adaptation, and population management strategies are essential to address the complex challenges of climate-induced migration.